Scott, Scotland, and Cuba: Transnational Literary Entanglements, Race, and a Cuban Anti-Slavery Novel. - Sood, Arun; Varona, Félix Flores (Scottish Literary Review)
In recent years a considerable body of scholarship on Scotland and the Caribbean has emerged, shedding light on previously neglected historical, literary, and economic entanglements. These important studies have primarily focused on the Anglophone Caribbean and former 'British West Indies', with much less attention paid to the links between Scottish writing and the Hispanophone Caribbean including Cuba, the largest island of the Greater Antilles. This article examines Walter Scott's Cuban reception and the related emergence of the Cuban anti-slavery novel. It begins with a broad survey of Scotland and Cuba's nineteenth-century literary entanglements before offering a short reception history of Scott in Cuba, culminating in a discussion of race in Waverley and Gertrudis Gómez de Avellaneda's Cuban anti-slavery novel Sab (1841).